Guía De Evaluación Por Resultados En El Aprendizaje De Cinemática Y Su Incidencia En El Rendimiento De Los Estudiantes De Ingeniería En Biotecnología Ambiental - Pumalema Morocho Blanca Fabiola; Borja Saavedra Myrian Cecilia; Cuadrado Pumalema Coralia Fabiola (European Scientific Journal, ESJ, 2018)
The objective of the research was to analyze the most appropriate approach to evaluate kinematics learning of first semester students in Engineering Environmental Biotechnology School of Chemical Sciences at the Escuela Superior Politecnica of Chimborazo. To do this, a theoretical framework was established based on didactics and curriculum theory. The investigation was correlational, explanatory and field. The Delphi method was used for consult of experts, who contributed synergistically to give a suitable answer to the research problem. A non-random sample of 24 students from a population of 68 was considered. To test the specific hypotheses, the Chi-square test statistic was used determining that the most appropriate kinematics evaluation approach to apply in the experimental group is by results through indicators of cognitive and affective domain, which positively affects the performance of students in the context of research. Because evaluation is a learning tool and an action-oriented organizational process to improve academic activities and obtain better results in the future, it is recommended to contrast evaluation by learning outcomes with evaluation by objectives or competences.